Directions for Supporting Green Projects in Sustainable Development (KIUT Publication, 2025)
In the sustainable development of our country’s economy, priority is given to the accelerated socio-economic development of regions. In the Development Strategy of “New Uzbekistan” for 2022–2026, the task was defined as “developing regional development programs annually based on comprehensive socio-economic development programs, with an in-depth study of the problems and opportunities of each district and city.” This indicates that in the coming years as well, priority in ensuring the sustainable development of our country’s economy will be given to regional reform programs.